The anticancer effect of PQ1 in the MMTV‐PyVT mouse model. Issue 6 (19th September 2013) - Shishido, Stephanie N.; Delahaye, Adélaïde; Beck, Amanda; Nguyen, Thu Annelise
<x xml:space="preserve">Abstract</x> Animal models are commonly used to analyze the mechanism of carcinogenesis as well as the development and screening of potent drugs. Here the transgenic strain FVB/N‐Tg(MMTV‐PyVT)634Mul/J (also known as PyVT) was used as a model system for measuring tumor burden, drug sensitivity, and metastasis of mammary carcinomas. Loss of gap junctional intercellular communication and the down regulation of connexin expression are characteristic of neoplastic cells. The substituted quinoline, 6‐methoxy‐8‐[(3‐aminopropyl)amino]‐4‐methyl‐5‐(3‐trifluoromethyl‐phenyloxy)quinolone (PQ1), has been shown to restore GJIC and increase connexin expression in breast cancer cell lines while not affecting normal mammary cells, suggesting that it may provide effective anticancer treatment with less detrimental effects. The PyVT spontaneous mammary tumor mouse model was used to determine the biological and histological effects of PQ1 on tumorigenesis and metastasis at three stages of development: Pretumor, early tumor and late tumor formation. Treatment with PQ1 at all three stages of development significantly reduced tumor growth. PQ1 treatment further increased Cx43 expression during pre‐ and early‐tumor formation, while it prevented an increase in Cx46 expression during late stage tumor formation. This study shows that Cx43 expression and neoplastic cellular growth are inversely related, but that PQ1 can alter tumor growth through targeting gap junction proteins to prove clinical efficacy in the treatment of spontaneous mammary tumors.